Financial incentives for breast cancer screening undermine informed choice. (10th January 2022) - Bartholomew, Theodore; Colleoni, Mirela; Schmidt, Harald
Abstract : Theodore Bartholomew, Mirela Colleoni, and Harald Schmidt argue that the focus should be on decision making not uptake when the balance of benefit and harm is subjective